Prevalence and Factors Associated With Liver Fibrosis Among Adult HIV-Infected Patients Attending Urban and Rural Care Clinics in Uganda - Wekesa, Clara; Kirk, Gregory D.; Aizire, Jim; Benson, Eve-Marie; Karabarinde, Alex; Parkes-Ratanshi, Rosalind; Ocama, Ponsiano (Oxford University Press, 2020)
Liver fibrosis is common among HIV-infected patients. Risk factors vary by location. Understanding this variation may inform prevention strategies. We compared the prevalence and correlates of liver fibrosis among HIV-infected patients attending care clinics in Uganda. Methods. This was a cross-sectional study involving 2030 HIV-infected patients attending care clinics in urban and rural Uganda. Liver fibrosis was defined as liver stiffness measurement (LSM) >7.1 KPa. Proportions and correlates of liver fibrosis were assessed and compared using logistic regression stratified by gender and site. Results. Prevalence of liver fibrosis was higher among participants in the rural clinic (15% vs 11%; P = .017). History of tobacco use (urban P = .022; rural P = .035) and serologic evidence of hepatitis C infection (HCV; urban P = .028; rural P = .03) was associated with liver fibrosis in all men. Elevated liver transaminases (urban P = .002; rural P = .028) and increasing age (urban P = .008; rural P = .052) were risk factors among all women. Tobacco use among women was only a risk factor in those attending the rural clinic (P = .003), and detectable HIV viral load (P = .002) for men in the urban clinic. Conclusions. Liver fibrosis is prevalent among HIV-infected persons in Uganda. HIV viral suppression and avoiding tobacco may be strategies to prevent liver fibrosis and cancer risk.
Keywords: ART era; Fibroscan; HIV/AIDS; Liver fibrosis; Sub-Saharan Africa